A class of eukaryotic GTPase with a punctate distribution suggesting multiple functional replacements of translation elongation factor 1α - Keeling, Patrick J. (National Academy of Sciences, 2004)
Translation elongation factor 1α (EF-1α, or EF-Tu in bacteria) is a highly conserved core component of the translation machinery that is shared by all cellular life. It is part of a large superfamily of GTPases that are involved in translation initiation, elongation, and termination, as well as several other cellular functions. Eukaryotic EF-1α (eEF-1α) is well studied and widely sampled and has been used extensively for phylogenetic analyses. It is generally thought that such highly conserved and functionally integrated proteins are unlikely to be involved in events such as lateral gene transfer or ancient duplication and gene sorting, which would undermine phylogenetic reconstruction. Here we describe a GTPase called EF-like (EFL), which is very similar to, but also distinct from, canonical eEF-1α. EFL is found in a wide variety of eukaryotes (dinoflagellates, haptophytes, cercozoa, green algae, choanoflagellates, and fungi), but its distribution is punctate: organisms that possess EFL are not closely related to one another, and EFL appears to be absent from the closest relatives of organisms that do possess it. Moreover, in most genomes where EFL is present, canonical eEF-1α appears to be absent. Analysis of functional divergence suggests that, whereas EFL is divergent in general, putative functional binding sites involved in translation are not significantly divergent as a whole. Altogether, it appears that EFL has replaced eEF-1α several times independently. This finding could be an indication of an ancient paralogy or, more likely, eukaryote-to-eukaryote lateral gene transfer.